Estudo de caso: análise da qualidade de blocos intertravados de uma empresa de pré-moldados no município de Pau dos Ferros/RN - Nóbrega, Raísa Luana Medeiros (Universidade Federal Rural do Semi-Árido, 2018)
Nowadays, the urbanization process is accelerating a lot in Brazil, and consequently urban mobility is a challenge to be overcome. This scenario requires managers to plan an integrated, sustainable and responsive system to meet the demands of the inhabitants' mobility. In view of, the interlocked pavement emerged as an interesting alternative in the market, being a great solution to minimize this urban problem. This study covered an analyses starting in the production line and going to the final stage of product’s quality control process, the interlock blocks, of a small company in the city of Pau dos Ferros - RN. Throughout the study, the manufacturing method of the product in loco was analyzed, and the tests as well, such as granulometry and dosages of the materials following NBR 9781/2013 for concrete pieces for paving. It was noticed that the method of obtaining the materials that the company used was outside of the parameters that the norm established, because of the index of water absorption and the resistance to compression did not present satisfactory values in relation to the established standard, which proved the necessity of control in the production line. Although the visual inspection test of the products presented close to the desired one, they would have to meet all the requirements established by the standard to be used by the civil construction.
Keywords: Empresa de pequeno porte; Pavimento intertravado; Produtividade; Controle tecnológico; Small business; Interlocked floor; Productivity; Technological control; ENGENHARIAS::ENGENHARIA CIVIL